Theoria, praxis, and the contemplative life after Plato and Aristotle - Bénatouïl, Thomas.; Bonazzi, Mauro, 1973- (Philosophia Antiqua, 2012)
Studies of the notion of theoria and of the contemplative life have often been restricted to Plato and Aristotle. This volume shows that aspirations to contemplation and the life of the intellect survived long after the classical period, turning into topics of heated debates, powerful arguments and original applications throughout the Hellenistic, imperial, and late antique periods. The introduction attempts to reconstruct all the problems pertaining to the contemplative life in Antiquity, and the twelve papers, written by distinguished scholars, offer a thorough study of the appropriation, criticism and transformation of Plato's and Aristotle's positions on the contemplative life, including its epistemological and metaphysical foundation. The volume ranges from Theophrastus to the end of Antiquity, including Jewish and Christian authors, with a focus on Platonism from Cicero to Damascius.